Negotiating Cultural Authenticity in Diasporic Children’s Literature: A Multicultural Analysis of Crouching Tiger and Auntie Yang’s Great Soybean Picnic - Buntoro, Viola Gema; Ni Komang Ariani (Universitas Pamulang, 2025)
This study aims to examine how the protagonists experience and respond to cultural authenticity in two children’s books, Crouching Tiger by Ying Chang Compestine (2011) and Auntie Yang’s Great Soybean Picnic by Ginnie Lo (2012), from the perspective of multicultural literature. A qualitative approach employing textual and visual analysis is used as the primary method. The analysis focuses on both narrative elements and illustrations to explore how Chinese culture is preserved and adapted within diasporic contexts, drawing on Mingshui Cai’s (2002) theory of multicultural literature. The findings indicate that cultural authenticity is dynamically represented through the protagonists’ encounters with cultural boundaries and the negotiation of ethnic perspectives. Moreover, the protagonists respond to issues of cultural authenticity through cultural immersion and fidelity to cultural realities. The study concludes that cultural authenticity functions as a crucial element in fostering a sense of belonging and enhancing intercultural understanding within children’s literature.